APPLICATION OF MULTIPLE INTELLIGENCES IN DEVELOPING CREATIVITY OF LAZUARDI HIGH SCHOOL STUDENTS IN DEPOK (Indonesian Journal of Educational Development (IJED), 2024)
In the 21st era, we are facing the industrial revolution 4.0 which is based on information technology. To face these challenges, individuals need to master certain skills. Schools are considered as a place to develop intelligence and produce quality future generations. However, there is still discrimination in assessing student intelligence, which is often only measured in cognitive terms. The introduction of the concept of multiple intelligences can be a solution to overcome discrimination in the world of education. This research aims to evaluate the application of multiple intelligences by Lazuardi High School in Depok and its impact on the development of student creativity. The research method used is qualitative with direct observation in the school and interviews towards teacher and students of Lazuardi High School, Depok. The research results show that the application of multiple intelligences through teacher approaches and extracurricular activities can successfully develop student creativity. When students can express the intelligence they have, this reflects the creativity they show.